Recovery orientation among individuals with serious mental illness - Fernandez, Aaron; Tan, Kit-Aun; Masiran, Ruziana (Wiley-Blackwell Publishing, 2017)
In the present study, we examined differences between individuals with schizophrenia and individuals with neuroses in a suburban clinical sample with respect to recovery orientation. A sample of 100 psychiatric patients from one public hospital in Selangor, Malaysia participated in this study. Participants’ recovery orientation was assessed by the Recovery Assessment Scale Questionnaire. The Multivariate Analysis of Variance (MANOVA) was significant. Univariate tests further showed that there was a significant difference across two different diagnoses on reliance on others. In particular, individuals with neuroses had higher reliance on others than individuals with schizophrenia did. In an attempt to promote recovery orientation among individuals with serious mental illness, social connection and social support are domains that mental health care providers could target on.